Circular insights - charting Malaysia’s path to sustainable product design - Bahrudin, Fadzli Irwan; Liew, Yong Kian; Anuar, Hazleen (Nova Science Publishers, 2025)
Malaysian consumers today enjoy widespread access to high-quality products, ranging from those produced by large corporations and local manufacturers to affordable daily necessities imported from abroad. The rise of giant online shopping platforms has further revolutionised access to goods, offering everything from personal care items and household products to furniture, garments, and wearables, all at reasonable prices and often of commendable quality. This convenience and doorstep delivery have undeniably elevated the living standards of many. However, this abundance is emblematic of a linear economy model, where products, once they reach the end of their useful life, contribute to the growing waste crisis; a problem Malaysia is currently struggling to address. This chapter reflects on this scenario, examining the onsequences of a linear economy, explaining the principles of a circular economy, and exploring the concept of product obsolescence. It also highlights the challenges and opportunities in transitioning to a circular economy approach for product design in Malaysia, offering brief insights into how the country can move towards a more sustainable and regenerative future.